The seven sisters : a novel - Riley, Lucinda (Riley, Lucinda. Seven sisters series., 2015)
"Maia D'Aplièse and her five sisters gather together at their childhood home, 'Atlantis'--a fabulous, secluded castle situated on the shores of Lake Geneva--having been told that their beloved father, who adopted them all as babies, has died. Each of them is handed a tantalizing clue to her true heritage--a clue which takes Maia across the world to a crumbling mansion in Rio de Janeiro, Brazil. Once there, she begins to put together the pieces of her story and its beginnings"--